ANALISIS PENGUJIAN KEKUATAN TARIK DAN UJI KEKERASAN TERHADAP PENGELASAN GTAW PADA SAMBUNGAN KAMPUH MODEL V DENGAN VARIASI MEDIA PENDINGIN PADA BAJA ST 45: ANALYSIS OF TENSILE STRENGTH TESTING AND HARDNESS TEST ON GTAW WELDING TO MODEL V CLAMP JOINTS WITH VARIATIONS OF COOLING MEDIA ON ST 45 STEEL - Maulana Ahmad Ali Akbar; Zulfa Khalida; Devina Rosa; Alfian Hudan (Jurnal Teknik Mesin, 2025)
In the welding process it will produce excessive heat and in the slow cooling process it will form chromium carbide which precipitates on the grain. These deposits can cause a decrease in the physical and mechanical properties of a material. This research aims to determine the effect of tensile strength and hardness of material resulting from GTAW welding on ST 45 Steel on variations in cooling media. The research method used is quantitative experimental, where the specimens are welded and cooled with three cooling media, then tested for tensile and Vickers hardness to evaluate their mechanical properties. The results showed that the SAE 20 W-50 oil cooling media produced the highest Modulus Young value (average 1584.60 MPa) and the highest Vickers hardness (459.33 HVN), while air provided a higher Yield Strenght (368.72 MPa). Statistical analysis using ANOVA confirmed that the differences were statistically significant. The conclusion of this research shows that SAE 20 W-50 oil is most effective in increasing material hardness and stiffness, while air is superior in increasing tensile strength.